Hubungan Maternal Role Attainment dengan Kenaikan Berat Badan pada bayi BBLR - Siti Noviyanti Nanik; Diyah Arini; Qori’Ila Saidah; Dwi Ernawati; Faridah (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2025)
Introduction: Weight gain in LBW (Low Birth Weight) babies felt more incompatible with the target that should be achieved to pursue their growth and development to be the same as babies that born normally. This related to the achievement of the mother's role (Maternal Role Attainment) which is a developmental and interactional process where every time a mother touches her baby will create an ability to parenting and take care of her baby including forming roles. Objectives:  The purpose of this research is to analyze the relationship between Maternal Role Attainment with the weight gain in LBW babies at Neonate Poly in RSU Haji Surabaya Methods:  The design of this research is analytic obesity with cross sectional approach. The sampling technique uses simple random sampling. The population of this research was 35 mothers with LBW babies that controlled at Neonate Poly in RSU Haji Surabaya. The instrument that used was a questionnaire for the achievement of the mother's role and observation using a weight scale. Then the data were tested using the Rho Correlation Spearmen. Results: The result showed that 14 respondents (40.0%) had good mother’s role achievement and 21 LBW babies (60.0%) had compatible weight gain. The result obtain <0.001 (ρ <0.05), means that maternal role attainment is related to weight gain in LBW babies at Neonate Poly in RSU Haji Surabaya. Conclusions: The implication of this research is to give an idea to the mother and family with LBW babies that the achievement mother’s role to parenting her baby can be achieved if every factor of Maternal Role Attainment are fulfilled.